Targeted therapy of oncogenic-driven advanced non-small cell lung cancer: recent advances and new perspectives. (2nd April 2020) - Genova, Carlo; Rossi, Giovanni; Tagliamento, Marco; Rijavec, Erika; Biello, Federica; Cerbone, Luigi; Zullo, Lodovica; Grossi, Francesco
ABSTRACT: Introduction : The discovery of new actionable oncogenic drivers has led to the development of effective antineoplastic targeted agents in advanced non-small cell lung cancer (NSCLC). While the role of inhibitors of the epidermal growth factor receptor (EGFR), anaplastic lymphoma kinase (ALK), and ROS proto-oncogene 1 (ROS1) is widely acknowledged, other oncogenic drivers can be exploited as therapeutic targets. Areas covered : Our aim is to explore the therapeutic role of actionable oncogenic drivers, including well-established targets, such as EGFR, ALK, and ROS1, as well as less frequent drivers for which specific agents are at different stages of clinical development, such as MET, RET, BRAF, and NTRK. Expert opinion : Targeted agents have revolutionized the management of advanced NSCLC; in particular, novel agents and combinations targeting EGFR, ALK, ROS1, BRAF, and NTRK have become available and others are on their way. The molecularly driven approach to advanced NSCLC requires adequate tumor samples, as well as increasingly complex technologies designed to assess multiple targets on limited available tissue in an acceptable time-span. Furthermore, the role of other novel antineoplastic approaches, such as immunotherapy with immune checkpoint inhibitors, needs to be elucidated in the case of patients with oncogenic-driven NSCLC.